Solving Inverse Problems Interestingly - Rommel Real (International Journal of Applied Sciences and Smart Technologies, 2020)
Inverse problems deal with recovering the causes for a desired or given effect. Their presence across sciences and their theoretical study can be traced to a classic example. Moreover, their ill-posedness motivates computational methods to solve them, and we give a very humble introduction to them. In relation we discuss their active research trends!